Analysis of limit state of reinforced high performance hybrid fiber concrete deep beams with openings - Smarzewski, Piotr; Spaczyńska, Renata (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The article presents the analysis of the strength of reinforced deep beams with openings made of high performance hybrid fibre concrete – steel and polypropylene. We compared the results of the shear capacity of the analytically calculated values based on its own assessment of the theoretical capacity of the proposals deep beams members created by modifications of empirical formulas.